Democracy's double helix participation, equality and revolution in early modern Europe - Behrisch, Lars 1973- (Cambridge University Press, 2025)
"Where does our democracy come from? It is a composite of two very different things: a medieval tradition of political participation, pluralistic but elitist; and the idea of individual equality, emerging in the early modern period. This study explores their trajectories and their first convergence in American and French revolutions"--